Energy balance and efficiency in crop rotation systems - Ferreira, Henrique Giordani Martini (2021)
The production system model that has been adopted in most Brazilian regions, the soybean/second corn crop succession, has led to problems in water and soil conservation and favorable conditions for diseases, pests, and weeds in the agricultural system and, consequently, increasing its energy use. Crop rotation is an alternative to this production model, directly interfering with the problematic aspects of the crop succession system and, consequently, its energy balance. Therefore, this study aimed to identify the crop rotation system with the best energy balance and efficiency. The data on the quantity of inputs (seeds, fertilizers, pesticides, and fuel), labor, and grain yield used in the study were collected from a crop rotation experiment conducted at the experimental station of the Rural Development Institute of Paraná - IAPAR-EMATER, Londrina, PR, Brazil, from 2014 to 2020. The experimental design consisted of randomized blocks, with six treatments and four replications. The treatments consisted of T1 (second corn crop/soybean), T2 (white oat/soybean, triticale/corn, and wheat/soybean), T3 (rye + black oat/soybean, black oat + fodder radish/corn, and congo grass/soybean), T4 (canola/corn, crambe/corn; canola/soybean); T5 (buckwheat-fodder radish/corn, bean/soybean, and buckwheat-white oat/ soybean), and T6 (wheat/corn, canola/corn + congo grass, and bean/soybean). The different crop rotations and the traditional second corn crop/soybean system provided positive energy balance and efficiency, that is, they produced more energy than they consumed. The canola/corn, crambe/corn, and canola/soybean rotation systems had the highest energy balance and efficiency, with values of 866,442.27 MJ ha -1 and 10.27, respectively, mainly due to corn cultivation in the summer, which resulted in a higher energy return than the other grain-producing crops.